Genome-wide identification and expression analysis of the GRAS gene family in Dendrobium chrysotoxum - Zhao, Xuewei; Liu, Ding-Kun; Wang, Qian-Qian; Ke, Shijie; Li, Yuanyuan; Zhang, Diyang; Zheng, Qinyao; Zhang, Cuili; Liu, Zhong-Jian; Lan, Siren (Frontiers in Plant Science, 2022)
The GRAS gene family encodes transcription factors that participate in plant growth and development phases. They are crucial in regulating light signal transduction, plant hormone (e.g. gibberellin) signaling, meristem growth, root radial development, response to abiotic stress, etc. However, little is known about the features and functions of GRAS genes in Orchidaceae, the largest and most diverse angiosperm lineage. In this study, genome-wide analysis of the GRAS gene family was conducted in Dendrobium chrysotoxum (Epidendroideae, Orchidaceae) to investigate its physicochemical properties, phylogenetic relationships, gene structure, and expression patterns under abiotic stress in orchids. Forty-six DchGRAS genes were identified from the D. chrysotoxum genome and divided into ten subfamilies according to their phylogenetic relationships. Sequence analysis showed that most DchGRAS proteins contained conserved VHIID and SAW domains. Gene structure analysis showed that intronless genes accounted for approximately 70% of the DchGRAS genes, the gene structures of the same subfamily were the same, and the conserved motifs were also similar. The Ka/Ks ratios of 12 pairs of DchGRAS genes were all less than 1, indicating that DchGRAS genes underwent negative selection. The results of cis-acting element analysis showed that the 46 DchGRAS genes contained a large number of hormone-regulated and light-responsive elements as well as environmental stress-related elements. In addition, the real-time reverse transcription quantitative PCR (RT‒qPCR) experimental results showed significant differences in the expression levels of 12 genes under abiotic stress treatment, among which two members of the LISCL subfamily (DchGRAS4 and DchGRAS17) were most sensitive to stress. Taken together, this paper provides insights into the regulatory roles of the GRAS gene family in orchids.